The Political and Institutional Effects of Term Limits - Sarbaugh-Thompson, M. author. aut Link
XII, 241 p. 5 illus.
Keywords: Please note this is a 'Palgrave to Order' title. Stock of this book requires shipment from an overseas. It will be delivered to you within 12 weeks. This innovative volume examines the effects of term limits on electoral competition, campaign contributions, and the activities of the Michigan legislature with in-depth interviews with legislators.